Transformation ratio at wakefield excitation in dielectric resonator by sequence of rectangular electron bunches with linear growth of charge - Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2014)
Transformation ratio has been derived in the case of the wakefield excitation in a dielectric resonator by sequence of rectangular in longitudinal direction (the same charge along the bunch) electron bunches, whose charge is profiled according to linear dependence. Long periodic sequence of electron bunches has been built to increase the number of accelerated electrons. In this sequence, the short trains of rectangular in longitudinal direction profiled bunches − drivers alternate by accelerated “high-current” bunches. This long sequence provides a large transformation ratio and the same for all bunches decelerating wakefield. The coupling of transformation ratio with reduction rate of field after witness and coupling of transformation ratio with witness charge and driver charge in this sequence have been derived.